Gender equity in physical education: The use of language - Óscar del Castillo Andrés; Santiago Romero Granados; Teresa González Ramírez; María del Carmen Campos Mesa (Universidade Estadual Paulista (UNESP), 2014)
This study analyzed Spanish teachers' behavior and the transmission of gender stereotypes. We observed 48 physical education lessons given by four Spanish teachers (two men and two women). Descriptive codes, which were generated iteratively, were clustered, categorized, integrated, recoded, and re-categorized. They allowed us to identify four major themes related to the transmission of gender stereotypes of teachers: male generics, stereotyped expressions, nominative attention, and priority order. We used a coding sheet as well as audio and video recordings to register the categories. The Kruskal-Wallis test produced significance levels lower than .05, resulting in the rejection of the null hypothesis. Sexist behavior was found in the male generics, nominative attention, and priority order. However, we found no difference in stereotyped expressions.